Synergistic integrated design of an electrochemical mechanical polishing end-effector for robotic polishing applications - Abd El Khalick Mohammad (2020)
In this paper, we present a novel design of a robotic electrochemical mechanical polishing (ECMP) process. Firstly, the process is presented to replace the conventional ECMP process by a robotic-based one. The advantage of using industrial robots lies in their flexibility, reconfigurability, large workspace and low prices compared to the conventional systems. Secondly, a novel design of a force-controlled end-effector for this purpose is presented. The end-effector is integrated into a macro-mini robot polishing cell. The macro robot (an industrial robotic manipulator) is used to position the mini robot (the proposed end-effector) according to the workpiece profile while the mini robot controls the polishing force. The effectiveness of the proposed device to polish un-milled and milled surfaces has been examined through polishing experiments. The results demonstrate the effectiveness of the presented device to reduce the surface roughness and improve the reflectability and appearance.